Photocatalytic removal of hexavalent chromium by Fe doped g-C3N4 loaded with dispersed diatomite modified by electron beam bombardment. (15th September 2021) - Zhang, Jing; Zhang, Xuewei; Zhou, Tianqing; Huang, Yixuan; Zhao, Libing; Ren, Zhuo; Liu, Xiaoli; Chen, Liang; Shao, Yuyang; Ma, Xijun; Xie, Xingyong; Wu, Zhengyan
Abstract: In this study, the diatomite (DE) was firstly dispersed by the electron beam bombardment (EB) to form the modified diatomite (MDE), using as the carrier of the Fe doped carbon nitride (FGCN). The MDE/FGCN demonstrates broader light adsorption in the visible region and low recombination of photogenerated electron-hole, according to the results of spectroscopy techniques. Reduction of hexavalent chromium (Cr(VI)) in the aqueous solution was used to illustrate the photocatalytic ability of MDE/FGCN. Results showed that the MDE/FGCN-1:3 (Fe, 10%) composites with EB dose of 30 kGy exhibited stronger reduction efficiency with 98.3% of Cr(VI) in 100 min, which was almost 16.92 times higher than that of pure GCN for the reaction rate. Additionally, lower pH values could promote the Cr(VI) reduction, and the MDE/FGCN displayed great stability after four runs. Lastly, the electron and heat effects of EB were creatively used to analyze the dispersion mechanism of MDE. The higher photocatalytic ability of MDE/FGCN could be attributed not only the dispersion of MDE but also the charge trapping by Fe. This study will broaden the application of physical irradiation in the modification of carriers for the photocatalyst, which can be applied in the treatment of environmental pollutants. Highlights: Diatomite was modified by electron beam bombardment to be more dispersed. The dispersed diatomite was used as the carrier of the Fe doped carbon nitride. The composite demonstrates 98.3% of Cr(VI) reduction in 100 min. The electrostatic repulsion of MDE and the doped Fe play key roles. The electron-heat effect of EB plays a key role for the dispersed diatomite.